2020
DOI: 10.2196/17799
|View full text |Cite
|
Sign up to set email alerts
|

A Graded Exposure, Locomotion-Enabled Virtual Reality App During Walking and Reaching for Individuals With Chronic Low Back Pain: Cohort Gaming Design

Abstract: Background Chronic low back pain (cLBP) can interfere with daily activities, and individuals with elevated pain-related fear (also known as kinesiophobia or the fear of injury due to movement) can develop worse long-term disability. Graded exposure (GEXP) protocols use successive participation in avoided activities to help individuals overcome fearful movement appraisals and encourage activity. We sought to develop a series of GEXP virtual reality (VR) walking and reaching scenarios to increase the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Although all included articles were clinical trials, two were single armed studies, one study acting as a proof-of-concept and the other to further validate its specific VR program. Most (eight out of thirteen) articles justified their chosen sample size ranging from 13 participants ( 14 ), to 179 participants ( 21 ). On average, sample size was approximately 50.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all included articles were clinical trials, two were single armed studies, one study acting as a proof-of-concept and the other to further validate its specific VR program. Most (eight out of thirteen) articles justified their chosen sample size ranging from 13 participants ( 14 ), to 179 participants ( 21 ). On average, sample size was approximately 50.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-eight articles were initially identified by this strategy. Thirty articles were then excluded (11 were duplicates, 24 were excluded because they did not meet inclusion criteria), and so 13 total studies were included (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Search Strategymentioning
confidence: 99%
“…Hennesy et al [ 35 ] undertook a small feasibility trial testing a virtual reality app during walking and reaching for patients with chronic low back pain. In this graded exposure approach to the functional task, they found that patients were able to undertake more difficult tasks over the sessions, measured by rate of perceived exertion, without increasing their pain or fear of movement.…”
Section: Discussionmentioning
confidence: 99%
“…VR and AR applications could help patients overcome the fear of movement through exposition to activities perceived as painful ( 162 , 163 ). While patients are distracted by VR applications, therapists could also reproduce supposed painful movements and then make patients aware that the movements were executed with little or no pain.…”
Section: The Crossroads Between Mts Vr and Armentioning
confidence: 99%